Application of Empty Fruit Bunches of Oil Palm Compost and Phosphate Fertilizers in Sorghum Planting (Sorghum bicolor (L.) Moench) at Rubber Planting Strip - Oktri Fadhilah Nasution; T Irmansyah; Eva Sartini Bayu (Universitas Sumatera Utara, 2017)
The aim of the research was to know the effect of empty fruit bunches of oil palm (EFBOP) compost and phosphate fertilizers in sorghum planting (Sorghum bicolor (L.) Moench) at rubber planting strip. Research was conducted at Sei Putih Research Institute, Galang, Medan with altitude ± 80 meters above sea level from April until August 2015, using randomized block design with two factors : EFBOP compost (without EFBOP, 7.5kg/plot and 15 kg/plot) and phosphate fertilizers (without fertilizer, 37.5 g/plot, 75 g/plot and 112.5 g/plot).Observed paramaters were plant height, number of leaves, diameter of stem, days of flowering, panicle number per sample, panicle number per plot and weight of 1000 seeds. The results showed the treatment of EFBOP compost had a significant effect to the plant height at 6,7,8,9, and 10 weeks after planting and number of leaves at 5,6,7, and 8 weeks after planting, best result at application of EFBOP compost range between T1 - T2 (7.5 kg/plot – 15 kg/plot). Phosphate fertilizers had a significant effect to the weight of 1000 seeds ,the number of panicle per sample, number of panicle per plot , phosphate fertilizer having optimum point at 60.93 g/plot – 62 g/plot.